2019
DOI: 10.29138/prd.v1i1.23
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Communication, Team Work, and Organizational Commitment on Improving Employee Performance at PT Seroja Lukindo Lestari Surabaya

Abstract: The purpose of this research is to determine the relationship between communication, team work, and organizational commitment to the performance of employees at PT Seroja Lukindo Lestari Surabaya. This research is using quantitative method. The population and sample based on questionnaires to employees of PT Seroja Lukindo Lestari Surabaya of 67 respondents. The method of data collection uses interviews, observations and questionnaires. Analysis of the data used validity test, reliability test, classic assumpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Facilities are physical facilities that provide convenience to users so that the needs of facility users can be met. It can be concluded that work facilities can incentivise employees to increase their work productivity and morale to achieve organizational goals (Auliyah & Artaya, 2019). Then, work discipline can be interpreted as a manager communicating his employees to change his behaviour to increase awareness and willingness to obey company rules and regulations (Suryawan & Salsabilla, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Facilities are physical facilities that provide convenience to users so that the needs of facility users can be met. It can be concluded that work facilities can incentivise employees to increase their work productivity and morale to achieve organizational goals (Auliyah & Artaya, 2019). Then, work discipline can be interpreted as a manager communicating his employees to change his behaviour to increase awareness and willingness to obey company rules and regulations (Suryawan & Salsabilla, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Facilities are physical facilities that provide convenience to users so that the needs of facility users can be met. It can be concluded that work facilities can incentivise employees to increase their work productivity and morale to achieve organizational goals (Auliyah & Artaya, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Organizational Commitment and Team Performance. If an organization pays more attention to the commitment of each member in it, in order to create conditions that are calm and comfortable, there can be an increase in terms of employee performance productivity (Anisah & Artaya, 2019). This is in line with Meutia & Husada's (2019) argument that commitment is a component of a strong sense of loyalty and love for an organization, consisting of different types of ties like emotional (affective), rational (normative), and future-focused (continuance) ties to create optimal performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The propensity of employees to actively participate and uphold membership in an organization is known as organizational commitment (Robbins & Judge, 2011;Hanaysha, 2016). Maximum performance and higher productivity are the results of high organizational commitment (Anisah & Artaya, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Fasilitas kantor adalah segala sesuatu yang terdapat dalam perusahaan yang ditempati dan dinikmati oleh karyawan baik dalam hubungan langsung maupun untuk kelancaran pekerjaan. Fasilitas kerja merupakan pendukung dalam aktivitas fisik suatu organisasi , dan sedang digunakan dalam kegiatan normal kantor, memiliki masa manfaat relatif permanen dan memberikan manfaat untuk masa depan (Auliyah and Artaya. 2019).…”
unclassified